Construction of a Novel Constitutively Active Chimeric EGFR to Identify New Targets for Therapy - Hua Cheng; Robert R. Langley; Qiuyu Wu; Wenjuan Wu; Jie Feng; Rachel Tsan; Dominic Fan; Isaiah J. Fidler (Neoplasia: An International Journal for Oncology Research, 2005)
Tumor cells and tumor-associated endothelial cells express activated epidermal growth factor receptor (EGFR) due to production of EGF-related ligands in the tumor microenvironment. To investigate the effect of perpetual EGFR activation on endothelial cells, we developed a novel method to generate constitutively active EGFR. We fused the entire intracellular domain of the EGFR to the N-terminus of the CD3ζ component of the T-cell receptor signaling complex. Expression of the chimeric receptor CD3-EGFR in EGFR-deficient human embryonic kidney cells resulted in ligand-independent sustained EGFR phosphorylation and in the induction of Akt, mitogen-activated protein kinase, and signal transducer and activator of transcription 3 (Stat3). Next, CD3-EGFR, was stably expressed in murine brain endothelial cells where it signaled for the initiation of angiogenic programs, Stat3 activation, and continuous proliferation. A comparison between brain endothelial cells encoding CD3ζ and CD3-EGFR revealed that proangiogenic phenotype was modulated by the intracellular effector Stat3 and that suppression of this downstream target with the EGFR tyrosine kinase inhibitor PKI166 could revert this phenotype. Thus, our results validate the use of chimeric constitutively active receptors to replicate critical features observed in pathophysiological processes that can expedite the identification of novel therapeutic agents targeting EGFR activation and function.